Fenomena Mafia Peradilan terkait Independensi Kekuasaan Kehakiman dalam Perspektif Budaya Hukum di Indonesia - Candra Ulfatun Nisa; Nyoman Serikat Putra Jaya (Journal of Judicial Review, 2021)
The consequences of adopting the concept of the rule of law are given independent judicial coordination authority. In fact, this independence is very easily misused, because the ideal function of the court as law enforcement is related to deterioration until the term judicial mafia appears. The method of research using the normative juridical approach, with descriptive research specifications. The results of this study are the judicial mafia which is identical with financial-oriented behavior in a way that allows to improve the course of law enforcement. The judicial mafia implies law enforcement over freedom of values, and is contaminated by factors outside the legal factor, thus clearly undermining the independence of judicial power and destroying the legal culture in Indonesia. First the culture "decides" to issue bribes because it considers the notion that the law can always be traded. As if the judicial mafia, has become an “icon” or “trademark” for irregularities in the informal law enforcement process that must be accepted as something common.